Effects of cation superstructure ordering on oxygen redox stability in O2-type lithium-rich layered oxides. Issue 2 (25th January 2023) - Eum, Donggun; Jang, Ho-Young; Kim, Byunghoon; Chung, Jinkyu; Kim, Dokyung; Cho, Sung-Pyo; Song, Seok Hyun; Kang, Seongmin; Yu, Seungju; Park, Sung-O; Song, Jun-Hyuk; Kim, Hyungsub; et al.
Abstract : We report that the presence of superstructure ordering serves as an important building block in securing the long-term stability of the oxygen redox activity in O2-type lithium-rich layered oxides. Abstract : Archetypical layered oxide with oxygen redox capability bears an additional lithium ion in a transition metal layer, and its local coordination with oxygen is crucial in triggering the oxygen redox activity. These additional lithium ions can form unique cation configurations such as honeycomb- or ribbon-like ordering depending on the species of transition metals, or dopants and the overall composition. Herein, we demonstrate that the presence of this superstructure ordering serves as an important building block in securing the long-term stability of the oxygen redox activity in O2-type lithium-rich layered oxides, which has been recently shown to be structurally robust against the voltage decay issue. It is revealed that the loss of the superstructure ordering by the aliovalent cation substitution of Co 3+ makes the layered structure more vulnerable to in-plane and out-of-plane transition metal migrations upon repeated cycles, thereby prompting a gradual decay in the oxygen redox activity even in O2-type layered oxides. On the other hand, Ni 2+ substitutions help preserve the superstructure cation ordering, and are capable of retaining the initial high-voltage oxygen redox activity (∼3.4 V vs. Li/Li + ) along with a high discharge capacity (∼239 mA h g −1 ). It is further elucidated how the macroscopic lithium de-/intercalation kinetics and the power capability of the lithium-rich electrodes can be affected by the cation ordering and the type of the substituents. These findings indicate the significance of the initial cation configuration in lithium-rich layered oxides, which is known to be dependent on the substituent and its composition, with respect to the oxygen redox stability, thereby offering guidelines for compositional engineering of lithium-rich layered oxides toward stable and reversible oxygen redox activity.